Tratamiento conservador de la ruptura prematura de membranas en parto pretérmino y su impacto en la morbilidad neonatal en el Hospital General Martín Icaza, periodo de abril - septiembre 2024. - López Estrada, Jasmany Francisco (2024)
Preterm premature rupture of membranes is a complication of pregnancy. This condition implies that the sac (aminiotic membrane) that surrounds your baby breaks (rupture) before 37 weeks of pregnancy. There are many treatments that are based on administering antibiotics to patients. This work aims to determine what influences the conservative treatment of premature rupture of membranes in preterm birth and its impact on neonatal morbidity at the Martín Icaza General Hospital, period May - September 2024, for which a mixed research design is applied, that is, it is qualitative and quantitative, transversal when referring to a specific period of time, with a descriptive approach, analytical-synthetic and inductive-deductive methods, of an exploratory type, using the documentary modality for the collection of theoretical and field information for the application of surveys to a population of 48 patients who were treated at the Martín Icaza general hospital in the period April - September 2024, obtaining as results that the patients with the highest incidence are between 15 and 30 years old, followed by patients over 30 years old. of age, while premature rupture of the membrane occurs with a higher incidence between 34 and 40 weeks of gestation, they received conservative treatment, few babies presented neonatal complications and there were no fetal losses.